Drying of Sodium Bicarbonate with Microwave Energy - SEYRANKAYA, ABDULLAH (Asian Journal of Chemistry, 2010)
Drying of sodium bicarbonate (NaHCO3) with microwave energy was investigated in this study. In industrial applications, sodium bicarbonate is dried in steam tube rotary or fluidized bed dryers by heating with air below 60 ºC. However, drying in rotary dryers is slow due to limitations in mixing and low gas temperatures. Higher temperatures are not permitted due to possible degradation of the product. Fluidized bed dryers cause dusting and powder formation as a result of attrition caused by collision of particles in the bed. Using microwave energy, sodium bicarbonate powder containing 7 and 15 % moisture was dried using microwave powers ranging from 136 to 800 W and 2450 MHz frequency at different layers of sample thicknesses. Sodium bicarbonate samples with 7 % initial moisture and about 2 mm sample thickness were dried successfully at all powers with no decomposition or disintegration of the crystalline molecules. Decomposition and caking of the product started to occur at 15 % initial moisture content and increased sample bed thicknesses (> 2 mm) at all power levels used.